THE EFFECT OF PERFORMANCE ASSESSMENT AND GRAMMAR MASTERY UPON THE WRITING ABILITY OF THE FOURTH SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM OF FKIP UNMAS DENPASAR IN THE ACADEMIC YEAR 2012/2013 - Murtini, N, Wersi; Padmadewi, M.,; A., J., N, N., Putra, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed to investigate the effect of performance assessment and grammar mastery upon the studentsâ writing ability. The research method used in this research was experimental. The population was 6 classes consisted of 180 students of the fourth semester students of the English Education Study Program of FKIP UNMAS Denpasar in the academic year 2012/2013. The sample of this study was 60 students which was divided into 2 groups, namely experimental and control group, by Cluster Random Sampling Technique. The research instruments used to obtain the data in this research were in form of tests which were analyzed using Statistical Two-Way ANOVA and Tukey Test. The research findings are first, there is a significant effect of performance assessment on the writing ability of the fourth semester students of the English Study Program of FKIP Unmas Denpasar in the academic year 2012/2013. Second, there is a significant effect of grammar mastery on the writing ability of the fourth semester students of the English Study Program of FKIP Unmas Denpasar in the academic year 2012/2013. Third, there is a significant effect of performance assessment and grammar mastery on the writing ability of the fourth semester students of the English Study Program of FKIP Unmas Denpasar in the academic year 2012/2013. Fourth, there is a significant effect between the students who have high grammar mastery assessed using performance assessment and assessed using conventional technique. Fifth, there is no significant effect between the students who have low grammar mastery assessed using performance assessment and assessed using conventional assessment technique. Â Keywords: Performance assessment, grammar mastery, writing ability.